Optimization of roller shape for roller-type onion pot-seeding machine - Hwang, Seok-Joon; Nam, Ju-Seok (International Journal of Agricultural and Biological Engineering, 2020)
In this study, roller shape optimization was performed on a roller-type pot-seeding machine used for sowing onion seeds. The parameters for optimization were derived by analyzing the operating characteristics of the pot-seeding machine. Based on this, the roller shape was determined to minimize weight while satisfying the required strength. When the optimized roller shape was applied, it was possible to reduce the weight of the roller by 17.7% compared with the conventional one, while satisfying the safety factor of 2.0 or more. The optimum bed soil compaction required for onion sowing was also obtained. Therefore, applying the roller shape derived from this study to an existing roller-type pot-seeding machine may increase the production efficiency of healthy seedling.Keywords: onion, pot-seeding machine, roller-type, shape optimizationDOI: 10.25165/j.ijabe.20201301.3897Citation: Hwang S-J, Nam J-S. Optimization of roller shape for roller-type onion pot-seeding machine. Int J Agric & Biol Eng, 2020; 13(1): 111–119.